2008
DOI: 10.1080/05704920802108115
|View full text |Cite
|
Sign up to set email alerts
|

Application and New Developments in Fluorescence Spectroscopic Techniques in Studying Individual Molecules

Abstract: Techniques based on fluorescence have played a variety of roles in chemistry, physics, spectroscopy, medicine, nanotechnology, and biotechnology due to their high selectivity, sensitivity, simplicity, and fastness in spectroscopic and imaging measurements. While detecting fluorescence from individual molecules by fluorescence-based techniques, poor signal, limited lifespan of fluorophores, trade-off between time resolution, and the level of detail of information were few major concerns. Ultrasensitive detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…These dyes have also found application in optical recording media in laser disks, laser dyes and optical sensitizers in various other fields as well as in molecular electronics. However, much interest has recently focused on application of these dyes as fluorescent probes for biomedical imaging [22][23][24] and single molecule studies [25][26][27][28][29]. Among cyanine dyes, merocyanine dyes have been broadly investigated to establish relationships between solvent polarity and photophysical behavior in the probe molecules and it was observed that these dyes possess large solvatochromic shifts, second-order hyperpolarizability, and are usefulness in diagnostics and therapeutics [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…These dyes have also found application in optical recording media in laser disks, laser dyes and optical sensitizers in various other fields as well as in molecular electronics. However, much interest has recently focused on application of these dyes as fluorescent probes for biomedical imaging [22][23][24] and single molecule studies [25][26][27][28][29]. Among cyanine dyes, merocyanine dyes have been broadly investigated to establish relationships between solvent polarity and photophysical behavior in the probe molecules and it was observed that these dyes possess large solvatochromic shifts, second-order hyperpolarizability, and are usefulness in diagnostics and therapeutics [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Triazines and their derivatives are important heterocyclic compounds widely used as the intermediate for the synthesis of chemical reagents, commercial medicines, pesticides, and so on [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. With the help of the triazines derivatives, the conjugated azacyanine (N,N’-methylene-2,2′-azapyridocyanine iodide) structure has shown excellent fluorescence property when applied in biological detection, such as in targeting human telomeric DNA by using azacyanine as a detection fluorophore [ 6 ] or single-molecule studies [ 9 , 10 , 11 ]. All these advantages have been widely researched since 1973.…”
Section: Introductionmentioning
confidence: 99%
“…The EEM spectrum is the carrier to realize the visualization of fluorescent compounds, so it is also called “fluorescence fingerprint (FF)” . Benefitting from sophisticated instrumentation, robust electronics, and computational power, the FF technique possesses high sensitivity in detecting organic matter with low concentration . Because of this superiority, many previous studies confirmed that the FF technique could be used as a monitoring tool for early warning of a water pollution accident. , Moreover, fast, inexpensive, reagent-free, and little sample preparation are also advantages of the FF technique .…”
Section: Introductionmentioning
confidence: 99%